Discrepancy between cardiorespiratory system and skeletal muscle in elite cyclists after hypoxic training - Kime, R.; Karlsen, T.; Nioka, S.; Lech, G.; Madsen, O.; Saeterdal, R.; Im, J.; Chance, B.; Stray-Gundersen, J. (Dynamic Medicine, 2003)
The purpose of this study was to determine the effects of hypoxic training on the cardiorespiratory system and skeletal muscle among well-trained endurance athletes in a randomized cross-over design. Methods: Eight junior national level competitive cyclists were separated into two groups; Group A trained under normoxic condition (21% O2) for 2 hours/day, 3 days/week for 3 weeks while Group B used the same training protocol under hypoxic condition (15% O2). After 3 weeks of each initial training condition, five weeks of self-training under usual field conditions intervened before the training condition was switched from NT to HT in Group A, from HT to NT in Group B. The subjects were tested at sea level before and after each training period. O2 uptake ( 02), blood samples, and muscle deoxygenation were measured during bicycle exercise test. Results and Discussion: No changes in maximal workload, arterial O2 content, O2 at lactate threshold and O2max were observed before or after each training period. In contrast, deoxygenation change during submaximal exercise in the vastus lateralis was significantly higher at HT than NT (p < 0.01). In addition, half time of oxygenation recovery was significantly faster after HT (13.2 ± 2.6 sec) than NT (18.8 ± 2.7 sec) (p < 0.001). Conclusions: Three weeks of HT may not give an additional performance benefit at sea level for elite competitive cyclists, even though HT may induce some physiological adaptations on muscle tissue level.